Burundi : Poverty Reduction Strategy Paper; Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses findings of the annual progress report on the Poverty Reduction Strategy Paper for Burundi. The report reveals that a number of decisive steps have been taken to promote political governance. Training sessions organized for local elected officials and members of parliament have contributed to enhancing their management capacities. With regard to the land tenure issue, the government expects to address it in the context of social cohesion so as to impart sustainable solutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet